Numerical Study for Unsteady Waves Generated by Flow over a Permeable Wavy Bed - Ikha Magdalena; Kemal Firdaus (Fluids, 2021)
In this paper, we formulate a numerical model to study unsteady waves generated by fluid flow over a permeable wavy bed. The model is derived from boundary value problems using potential theory. We solve the model numerically using a finite difference method. As a result, we found that the flow over a porous layer generates wave disturbed by bumps on the porous layer. The simulation also showed that the wave profile shifts from the permeable bed. The results of this study can be incorporated into the design of submerged artificial and natural breakwaters.